COMBINING ABILITY ANALYSIS FOR YIELD AND ITS COMBONENTS IN SUMMER SQUASH (Cucurbita pepo L.) - Shamil Y .H. Al-Hamdany (Mesopotamia Journal of Agriculture)
The experiment was carried out in the Horticulture and Landscape Research Field ,College of Agriculture and forestry , Mosul University ,in Spring and Autumn seasons of 2007 , to study the general and specific combining ability using Full-Diallel Crosses of four varieties in summer squash viz, 1-local (malea Ahmed) , 2-Syrian (Al-Mostkabil) , 3-Tala and 4-Bather- Eibethor and their F1 hybrids by Randomized Complete Block Design (R.C.B.D) with three replications. The results indicated that general combining ability was significant for: plant height, number of leaves/ plant, the date male flowering ,fruit length and diameter, number of fruits /plant and total yield , while specific combining ability was significant for: number of leaves/plant, the date male and female flowering ,percentage of flower ,fruit length and diameter , number of fruits /plant and total yield. The reciprocal effect was significant for all studied character except early yield. The results showed that general combining ability was higher than specific combining ability for plant height , it can be predicted for on additive gene action for this character. Syrian(AI-Mostkabil) variety showed high general combining ability for most of the studied characters ,and therefore contains the desired gene. The hybrids varied for their specific combining ability effects and this due to the wide genetic variation between the parents .